2011
DOI: 10.1038/mt.2010.239
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral Vector Platform for Production of Bioengineered Recombinant Coagulation Factor VIII

Abstract: Patients with hemophilia A present with spontaneous and sometimes life-threatening bleeding episodes that are treated using blood coagulation factor VIII (fVIII) replacement products. Although effective, these products have limited availability worldwide due to supply limitations and product costs, which stem largely from manufacturing complexity. Current mammalian cell culture manufacturing systems yield around 100 µg/l of recombinant fVIII, with a per cell production rate of 0.05 pg/cell/day, representing 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 19 publications
1
52
0
7
Order By: Relevance
“…Several strategies to enhance vector efficacy by modifications in the vector capsid or vector genomes, transgene optimization, and chimeric molecules are ongoing. [27][28][29][30] Here we sought to test liverbased gene therapy using AAV-FVIII-RH as a strategy to enhance endogenous FVIII expression levels and biological activity. Notably, circulating levels of FVIII-RH were higher than those in HA mice injected with AAV-FVIII-BDD at all 3-dose cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Several strategies to enhance vector efficacy by modifications in the vector capsid or vector genomes, transgene optimization, and chimeric molecules are ongoing. [27][28][29][30] Here we sought to test liverbased gene therapy using AAV-FVIII-RH as a strategy to enhance endogenous FVIII expression levels and biological activity. Notably, circulating levels of FVIII-RH were higher than those in HA mice injected with AAV-FVIII-BDD at all 3-dose cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Furthermore, we identified sequences within p-FVIII that are necessary and sufficient for the greater expression, 11 demonstrated that this differential occurs through reduced engagement of the unfolded protein response pathway, 10 and have used this information to generate humanized, human/porcine (HP) high-expression FVIII constructs that retain this biosynthetic advantage. 17,18 A similar strategy is being pursued in gene therapy applications for hemophilia B through the use of a naturally occurring human FIX variant termed FIX-Padua (R338L) that exhibits greater specific procoagulant activity than wild-type human FIX. Inclusion of this modified FIX has been shown to improve vector and transgene potency in preclinical AAV gene therapy studies.…”
Section: Origins and Limitations Of Fviii And Fix Biosynthesismentioning
confidence: 99%
“…This bioengineered FVIII transgene demonstrated equivalent transgene product expression to BDD p-FVIII in vitro and in vivo using both SIV-and HIV-based expression vectors. 11,17,18 An alternative, but also successful, preclinical HSCT gene therapy strategy incorporating nonengineered BDD h-FVIII, and more recently FIX, transgenes involves specific targeting of transgene expression to the megakaryocyte/platelet hematopoietic lineage. This approach was first demonstrated by Poncz et al using transplantation of HSCs from transgenic mice to correct the hemophilia A bleeding phenotype.…”
Section: Multipotent Adult Stem Cell Therapies: Hscsmentioning
confidence: 99%
“…20 Retronectin is a recombinant human fibronectin fragment that increases the efficiency of lentiviral and retroviral transduction by binding both target cells and recombinant lentiviral or retroviral vector particles to facilitate gene transfer. Despite advances in vector production, 21 10-1000 ml of vector are still needed to treat each patient with a high enough efficiency. The scale and yield limitations of vector manufacture and the low efficiency of gene transfer are currently major barriers to the commercialization and widespread implementation of lentiviral vector-based gene therapy, which otherwise has the potential to cure many human diseases.…”
Section: Lentiviral Transduction Of Suspension Cellsmentioning
confidence: 99%